Methods for electrical stimulation control of lower limbs in individuals with spinal cord injury - Sousa, Ana Carolina Cardoso de (2019)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2019.